Colorimetric study of malvidin-3-O-glucoside copigmented by phenolic compounds: The effect of molar ratio, temperature, pH, and ethanol content on color expression of red wine model solutions. (December 2017) - Zhang, Bo; Yang, Xue-Shan; Li, Ning-Ning; Zhu, Xia; Sheng, Wen-Jun; He, Fei; Duan, Chang-Qing; Han, Shun-Yu
Abstract: In the recent research, the copigmentations of malvidin-3- O -glucoside with eight types of phenolic copigments have been investigated. The influence of the pigment/copigment molar ratio, the reaction temperature, the pH and the ethanol content of solutions has been examined. The results showed that the copigmentation effect was dependent on not only the particular structures of the phenolic compounds but also the factors of the reaction systems. The increase of the copigment concentration can strengthen the copigmentation effect, improve the solution color, and enhance the red-purple features. Different temperatures had different influences on the copigmentation reactions. The destruction of the copigmentation complexes can result in the hypsochromic shift of the reaction solution when the temperature was higher than 20 °C. The bathochromic shift of the solution gradually progressed with the increase of the pH value. A significant copigmentation feature was spotted when pH reached 3.0, which demonstrates obvious red-purple characterization. The addition of the ethanol weakened the copigmentation effect. According to measurement through color analysis, it was found that the color differences caused by ethanol in red wine were typically attributed to quantitative changes. Remarkably, all of the above delicate color deviations caused by the structural or environmental factors can be precisely and conveniently depicted via the CIELAB space analysis. Graphical abstract: Highlights: Colorimetric study of malvidin-3- O -glucoside copigmented by phenolic compounds. The structure characteristics of copigments were divided into three categories. The four factors of influencing copigmentation were investigated. The concentration and structure of the copigments affected the copigmentation. The addition of the ethanol weakened the copigmentation effect.